Strategies for Scaling Businesses in Emerging Markets: Case Study of the Paints and Coatings Industry in Kazakhstan and USA - Andrey Chshelokovskiy (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej)
This article analyzes how paints and coatings businesses in the USA and Kazakhstan scale between 2019 and 2023. The research employs a non-linear econometric model to identify key factors, including market size, innovation, supply chain efficiency and government policy, that affect business growth, in an analysis involving developed and emerging markets. Second, the author develop a Scaling Impact Index to provide a comparative metric to evaluate the scaling potential of businesses in both respective countries. Results demonstrate that although the USA is supported by existing infrastructure and technology innovation, Kazakhstan boasts great opportunities for growth, provided by market expansion and support from the government. The research calls to improve the infrastructure and to introduce innovation investments in Kazakhstan, while American business should maintain competition advantages. The results provide insights into the scaling dynamics of businesses operating in different economic environments, and are relevant both for business strategy, as well as policy formulation.